Envisioning America and the American self Republican and Democratic party platforms, 1840-2016 - Appelrouth, Scott 1965- (Routledge, 2019)
This book explores the Democratic and Republican Party platforms from 1840 to 2016. As the only official, institutionally sanctioned document espousing the parties' views on the state of the nation, the platforms present to the party faithful a diagnosis of what ails the country and the promise of possessing the necessary cure. In doing so, they offer more than a listing of specific issues in need of redress through legislative action, and moreover serve as a form of national storytelling through which political parties forge their vision of America and of what it means to be an American. Using topic modeling as an entry point into the documents, the author moves to consider more closely two related themes: those of how the platforms narrate the "American" self and individual freedom. With consideration of the extent to which the parties envision the self as an isolated economic actor or as an individual with a range of duties and obligations to a broader community, the spheres of action that they consider focal points for individual autonomy, and the extent to which they view liberty as freedom from restraint or freedom to act, this book sheds light on the historical trajectory of the growing fracture in American politics as well as the points of convergence across the two parties. Moreover, positing that behind their divisive rhetoric, both share a fundamental vision of what it means to be a "person," the author argues that perhaps their seemingly intractable differences are more a matter of degree than kind